User requirements for image-guided navigation in spinal surgery - Craven, Michael P.; Pecchia, Leandro; Martin, Jennifer L. (Springer, 2013)
Advances in image-guided technology have resulted in a number of technologies to support surgeons in the identification of tissue and the tracking and navigation of surgical instruments in spinal surgery. There are various existing and proposed systems to support registration and intra-operative image guidance based on fluoroscopy, Computerized Tomography (CT), Magnetic Resonance Imaging (MRI) and ultrasound (US) or combinations of imaging modalities. However, the user requirements for the design of such systems are complex, dependent on medical specialty in addition to the range of instrumented and non-instrumented treatments offered in the orthopedic and neurological domains. This paper presents a review and study of user requirements for intra-operative navigation in spinal surgery. The numerous outcomes measures for successful operations are outlined, that provide a basis for understanding the needs of surgeons. A hierarchy of needs is then presented that can be used to inform an Analytic Hierarchy Process for elicitation of detailed user requirements.